Safety and Health Monitoring System for Baby Incubator using IoT - Wahab, Muhammad Aiman; Md Nor, Danial (Evolution in Electrical and Electronic Engineering, 2021)
Temperature is an essential element of our surroundings in today's world. Temperature fluctuations may have a detrimental effect on all biological organisms and certain semiconductor materials. This project aims to offer temperature control for specific applications such as baby incubators. The internet of Things (IoT) is having a significant impact on the medical sector in infant incubators. To fulfill the requirement for remote control and monitoring, the use of wireless technologies is increasing. In this scenario, the doctor cannot constantly monitor a baby's pulse rate per minute and the temperature of the incubator. As a result, a doctor who was far away from the baby incubator found it impossible to determine the baby's heart rate and temperature for early therapy. This project describes the creation of a low-cost monitoring system that monitors the heartbeat and temperature of the infant in the incubator. The Arduino Uno microcontroller was used in this project. This project may be tracked with a smartphone and MIT Apps inventor. The data communication module is used to transmit information between people and machines. The communication module of the project is an ESP 8266, and the project requires an internet connection to monitor the parameter. Temperature control is accomplished via the usage of Arduino's programming code. LEDs are used to show temperature changes in infant incubators. IoT web design is used to monitor temperature and heartbeat changes in real time, regardless of location. Last, this project is focused on the idea of developing a Smart Monitoring Incubator System via IoT, which would allow medical staff to monitor their babies even when they are physically separated from them and can feel their every condition from any remote corner of the world.